Evaluation of Sampling Techniques in Audit: A Qualitative Approach - Santoso, Fadli; Wulandari, Indarsih; Pratiwi, Dinda (Golden Ratio of Auditing Research, 2023)
This study explores the evaluation of sampling techniques in audit engagements, aiming to provide insights into the factors influencing auditors' decisions and the effectiveness of different sampling methods. The research adopts a qualitative approach, conducting a comprehensive literature review to identify key themes and discussions surrounding sampling techniques in auditing. Factors such as population characteristics, audit objectives, resource constraints, audit complexity, regulatory requirements, and technological advancements are analyzed to understand their impact on sampling decisions. Through thematic analysis, the study identifies emerging themes, including the effectiveness of sampling techniques, factors influencing sampling decisions, and the role of technological advancements in audit sampling. Findings suggest that while traditional sampling methods like random sampling and systematic sampling remain prevalent, innovative approaches such as statistical sampling and probability-proportional-to-size sampling offer enhanced precision and reliability, particularly in complex audit environments. The integration of technology, particularly data analytics tools and audit software, has revolutionized audit sampling practices, enabling auditors to conduct more comprehensive and efficient sampling procedures. Overall, the study contributes to the existing body of knowledge on sampling techniques in auditing and provides practical implications for audit practitioners, researchers, and policymakers.